Small Bowel Pleomorphic Liposarcoma: A Rare Cause of Gastrointestinal Bleeding - Simon Nennstiel; Martin Mollenhauer; Christoph Schlag; Valentin Becker; Bruno Neu; Norbert Hüser; Ralf Gertler; Roland M. Schmid; Stefan von Delius (Case Reports in Gastrointestinal Medicine)
In this case report we present a 60-year-old male patient with overt midgastrointestinal bleeding of a primary ileal pleomorphic liposarcoma diagnosed by video capsule endoscopy (VCE). Clinical work-up for final diagnosis and the pathological background of this uncommon tumorous entity of the small bowel will be discussed in this paper.